Halla la tasa de variación de cada funcion en el intervalo [-4,3] e indica si es positiva , negativa o nula A) f(x)=x2-2x+4 B) f(x)= -3x + 2 En rl ejercico A es x elevado al 2 o cuadrado

Respuesta :

Answer:

[tex]A) \hspace{3}Rate\hspace{3}of\hspace{3}change=-5\hspace{3}Negative\\\\B)\hspace{3}Rate\hspace{3}of\hspace{3}change=-21\hspace{3}Negative[/tex]  

Step-by-step explanation:

Given a function [tex]f(x)[/tex], we called the rate of change to the number that represents the increase or decrease that the function experiences when increasing the independent variable from one value "[tex]x_1[/tex]" to another "[tex]x_2[/tex]".

The rate of change of [tex]f(x)[/tex] between [tex]x_1[/tex] and [tex]x_2[/tex] can be calculated as follows:

[tex]Rate\hspace{3}of\hspace{3}change=f(x_2)-f(x_1)[/tex]

For:

[tex]f(x)=x^2-2x+4[/tex]

Let's find [tex]f(x_1)[/tex] and [tex]f(x_2)[/tex], where:

[tex][x_1,x_2]=[-4,3][/tex]

[tex]f(x_1)=f(-4)=(-4)^2-2(4)+4=16-8+4=12\\f(x_2)=f(3)=(3)^2-2(3)+4=9-6+4=7[/tex]

So:

[tex]Rate\hspace{3}of\hspace{3}change =7-12=-5\hspace{3}Negative[/tex]

And for:

[tex]f(x)-3x+2[/tex]

Let's find [tex]f(x_1)[/tex] and [tex]f(x_2)[/tex], where:

[tex][x_1,x_2]=[-4,3][/tex]

[tex]f(x_1)=f(-4)=-3(-4)+2=12+2=14\\f(x_2)=f(3)=-3(3)+2=-9+2=-7[/tex]

So:

[tex]Rate\hspace{3}of\hspace{3}change =-7-14=-21\hspace{3}Negative[/tex]

Translation:

Dada una función [tex]f(x)[/tex], llamábamos tasa de variación al número que representa el aumento o disminución que experimenta la función al aumentar la variable independiente de un valor "[tex]x_1[/tex]" a otro "[tex]x_2[/tex]".

La tasa de variación de [tex]f(x)[/tex] entre [tex]x_1[/tex] y [tex]x_2[/tex], puede ser calculada de la siguiente forma:

[tex]Tasa\hspace{3}de\hspace{3}variacion=f(x_2)-f(x_1)[/tex]

Para:

[tex]f(x)=x^2-2x+4[/tex]

Encontremos [tex]f(x_1)[/tex] y [tex]f(x_2)[/tex], donde:

[tex][x_1,x_2]=[-4,3][/tex]

[tex]f(x_1)=f(-4)=-3(-4)+2=12+2=14\\f(x_2)=f(3)=-3(3)+2=-9+2=-7[/tex]

Entonces:

[tex]Tasa\hspace{3}de\hspace{3}variacion =7-12=-5\hspace{3}Negativa[/tex]

Y para:

[tex]f(x)-3x+2[/tex]

Encontremos [tex]f(x_1)[/tex] y [tex]f(x_2)[/tex], donde:

[tex][x_1,x_2]=[-4,3][/tex]

[tex]f(x_1)=f(-4)=-3(-4)+2=12+2=14\\f(x_2)=f(3)=-3(3)+2=-9+2=-7[/tex]

Entonces:

[tex]Tasa\hspace{3}de\hspace{3}variacion=-7-14=-21\hspace{3}Negativa[/tex]

ACCESS MORE